2010 International Conference on Advances in Computer Engineering 2010
DOI: 10.1109/ace.2010.20
|View full text |Cite
|
Sign up to set email alerts
|

Linear Prediction Modelling for the Analysis of the Epileptic EEG

Abstract: Epilepsy is a chronic neurological disorder characterized by recurrent, unprovoked seizures. This study deals with a preliminary investigation to detect epileptic components in the electroencephalogram (EEG) waveform, which results in a reduction of analysis time by the expert neurologist. As an alternative to the Fast Fourier Transform (FFT) spectral analysis approach, an Auto Regressive (AR), a Moving Average (MA) and an Auto Regressive Moving Average (ARMA) model-based spectral estimators can be used to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Khan et al [9] have applied wavelet transform for preprocessing. Other methods of noise removal from EEG signals include surrogate channel [56] with the help of common spatial pattern filtering [57], local mean decomposition [54] and adaptive filtering [58], [59].…”
Section: A Pre-processingmentioning
confidence: 99%
“…Khan et al [9] have applied wavelet transform for preprocessing. Other methods of noise removal from EEG signals include surrogate channel [56] with the help of common spatial pattern filtering [57], local mean decomposition [54] and adaptive filtering [58], [59].…”
Section: A Pre-processingmentioning
confidence: 99%
“…15 Some researchers were keen about the selection of the database as well. Numerous studies have been conducted for the prediction and detection of seizures, such as using linear prediction, 18 using cloud computing technology, 19 using deep learning methods, 20 using wavelet packets, 21 etc. Majority of the previous studies as in other works 3,4,17 were analyzed and found that due to the uncorrelated data used, the results are not consistent.…”
Section: Related Workmentioning
confidence: 99%
“…Majority of the previous studies as in other works 3,4,17 were analyzed and found that due to the uncorrelated data used, the results are not consistent. Numerous studies have been conducted for the prediction and detection of seizures, such as using linear prediction, 18 using cloud computing technology, 19 using deep learning methods, 20 using wavelet packets, 21 etc. Various challenges in identifying the correct seizure for epilepsy were also studied extensively.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is often called as the Auto Regressive method of frequency determination [12]. The Auto Regressive way tends to define the frequency spectra of the signal as 'peaky',(signal which has peaks present for the Power Spectral Density curve at specific frequencies) [12].…”
Section: Linear Prediction Coding (Lpc)mentioning
confidence: 99%